The dairy-free cook book over 50 delicious recipes that are free from dairy products - Pannel, Maggie (Healthy eating library, 1999)
Healthy eating is all about enjoying a good variety of foods so that we obtain all the essentials nutrients needed for growth and repair and for maintaining all the bodily processes that keep us fit and well. Food choice itself it not always governed by personal preference and people who suffer from lactose intolerance or milk allergy are faced with a major problem of finding a nutriutious and tasty dairy free diet. However, if you have been diagnosed as intolerant or allergic to dairy foods (or just choose to follow a Vegan diet which excludes all animal products), the good news is that there are plenty of delicious alternatives available. "The Dairy Free Cookbook" is designed to give you the help, advice and information you need plus lots of dairy free recipes for you, your friends and family to enjoy.